MR of the inner ear in patients with Cogan syndrome. - Casselman, J W; Majoor, M H; Albers, F W (American Journal of Neuroradiology, 1994)
PURPOSE To determine whether the bony and soft-tissue obliterations of the intralabyrinthine fluid spaces reported in pathologic studies of patients with Cogan syndrome can be detected with MR or CT. METHODS The inner ears of six patients with Cogan syndrome were studied. High-resolution CT was performed in five patients; all six patients were studied with MR, including T1-weighted spin-echo images with and without gadolinium administration, T2-weighted spin-echo images, and three-dimensional Fourier transform constructive interference in steady state images. RESULTS In two patients, small calcified obliterations were detected on CT but the three-dimensional Fourier transform constructive interference in steady state images revealed more extensive soft-tissue obliteration in five of the six patients. High signal inside the membranous labyrinth on precontrast T1-weighted images and contrast enhancement inside the membranous labyrinth on the postcontrast T1-weighted images were seen in one patient. CONCLUSIONS The study showed that calcific obliteration and soft-tissue obliteration of the intralabyrinthine fluid spaces in patients with Cogan syndrome can be demonstrated radiologically and that soft-tissue obliteration is more frequent than calcified obliteration. MR detected the intralabyrinthine disease far more frequently than did CT. The three-dimensional Fourier transform constructive interference in steady state sequence proved to be the most sensitive MR sequence. Hyperintensity inside the membranous labyrinth on the precontrast T1-weighted images and enhancement on the contrast-enhanced T1 images were less frequent and probably represent leakage through the abnormal labyrinthine membrane from active disease.